Konseling Logoterapi: Penetapan Tujuan Hidup Remaja Broken Home di MAN 4 Banyuwangi - Nisa, Fiqri Zuhrotun; Anikoh, Indifatul (Lembaga Yasin AlSys, 2025)
This study was motivated by the limited studies on the determination of life goals in adolescents from broken homes. In fact, this phenomenon has a significant impact on the psychological development and life direction of adolescents, especially in high school education. The purpose of this study was to explore the process of determining life goals through a logotherapy counseling approach in a student who experienced an existential crisis due to her incomplete family condition. The method used was qualitative with a case study design, with one participant, namely Nadia (pseudonym), a class XII student at MAN 4 Banyuwangi who was selected through purposive sampling techniques. Data were obtained through in-depth interviews, participant observation, and documentation, then analyzed using thematic analysis techniques. The results showed that logotherapy counseling played an important role in helping Nadia re-arrange the meaning of her life and set more positive and realistic goals. Logotherapy techniques such as Socratic dialogue, value reflection, and meaning-finding proved effective in forming self-understanding and new life directions for participants. These findings are in line with the objectives of the study and strengthen Viktor Frankl's theory on the importance of meaning in overcoming psychological suffering. The main conclusion of this study is that logotherapy has great potential in helping adolescents from broken homes find meaning in life and set constructive long-term goals. The implications of this study include theoretical aspects, namely contributions to the literature on meaning-based counseling in the context of adolescents in Indonesia, as well as practical aspects in the form of recommendations for the application of logotherapy in school environments by counselors to support students' mental health. This study also opens up opportunities for further studies on the effectiveness of logotherapy in group formats and its long-term impacts.